SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT NASABAH DENGAN METODE AHP (Analytical Hierarchy Process) PADA PT. CIMB NIAGA AUTO FINANCE KUDUS (Information Technology and Telematics, 2014)
Abstrak In line with the companies, there are many customers or employers who submit credit to PT. Cimb Niaga Auto Finance Kudus. These matters demanding bank should increase service quality to customer. Purpose design of this system is designing and constructing support system decision that could help the bank in determining feasibility credit provision to customer. Development support system decision using methods analytical hierarchy process (AHP) as one method decision-making solving a problem multikriteria. Development this system uses visual basic 6.0 with database mysql. Analysis used in determining feasibility credit provision PT. Cimb Niaga Auto Finance Kudus apply analysis 5c (character, capital, capacity, collateral and condition of economy). Key words: decision support systems, granting credit, MySQL, Visual Basic.